Papillary renal cell carcinoma with testicular and penile metastases: A case report and literature review - Safriadi, Ferry (Urol Case Rep, 2020)
The most common site of Metastatic Renal Cell Carcinoma (mRCC) are lung, bone, liver, and brain. We report an extremely rare case of a 69-year-old man who presented mRCC to testicle and penis. He had a left-sided testicular mass in addition to left-sided abdominal fullness. He underwent a percutaneous renal biopsy with pathologic result was papillary RCC. The patient started on targeted therapy with Lenvatinib. Because there was no progress in this treatment, the patient came to our clinic. Subsequently, we performed left cytoreductive nephrectomy and radical left orchiectomy, and total penectomy. The definitive pathologic result confirmed papillary RCC.